Perjanjian Berdarah: Jejak Kerukunan dan Toleransi dalam Peradaban Islam di Kerajaan Kutaringin - Nursalam Ihsan Insan Budiman; Rambli Rambli; Nur Winda Maysara (Departement of Mathematics Education, 2024)
This research seeks to analyze harmony and tolerance in Islamic civilization in the Kutaringin Kingdom which is analyzed from the perspective of the Koran. Analysis of the values ​​of harmony and tolerance regarding the bloody treaty incident and the implications of religious and cultural shifts in the view of the Koran. The method used in this research is a qualitative-descriptive approach with a literature review or literature study method. The results of this research show that during the bloody agreement which was the beginning of the formation of the Kutaringin kingdom, there was a high value of harmony which can be seen from the meaning of the bloody agreement, namely that the Arut Dayak tribe accepted diplomacy from the prince, the desire of the Arut Dayak to be treated fairly and with mutual respect, uniting all feelings. and thoughts, and build a kingdom together. To analyze the value of harmony, the author relies on Surah al-Hasyr verse 9. Then the role of the cleric Kiyai Gede in spreading Islam was to follow the way of the Prophet's preaching, so that Islam developed rapidly and society had strong unity even though there were ethnic differences as in Surah Al-Baqarah verse 256. This has resulted in a cultural shift that occurs, such as when people die, some people have buried the bodies, different from before where there was still the traditional tradition of besandai (being propped up under a big tree in the forest). This indicates that there is a strong value of tolerance in the Dayak tribe. The flow and influence of the Kutaringin Kingdom which is based on Islam. The current government system can adopt the implementation pattern implemented by the Kutaringin kingdom, namely prioritizing unity.